The potential for malignancy from atopic disorders and allergic inflammation: A systematic review and meta‐analysis. Issue 2 (20th December 2019) - Muir, Amanda B.; Whelan, Kelly A.; Dougherty, Michael K.; Aaron, Bailey; Navarre, Brianna; Aceves, Seema S.; Dellon, Evan S.; Jensen, Elizabeth T.
Abstract: Objective: While chronic inflammation is a well‐established risk factor for malignancy, studies evaluating the relationship between allergic inflammation and cancer have revealed conflicting results. Here, we aimed to assess the association between allergic inflammation in the lung (asthma), skin (eczema) or oesophagus (eosinophilic oesophagitis; EoE) and cancer at the organ site. Design: We conducted a systematic review of the literature to identify observational studies (case‐control, cohort and cross‐sectional) evaluating the association between asthma and lung cancer, eczema and skin cancer, or EoE and oesophageal cancer. Random‐effects meta‐analysis was performed to define pooled estimates of effects. Data sources: PubMed, EMBASE and Web of Science. Eligibility criteria for selection: Included studies evaluated the incidence of cancer. Results: Thirty‐two studies met the inclusion criteria, 27 in the lung, four in the skin and one in the oesophagus. Meta‐analysis of the three studies with prospective data collection of asthma diagnosis revealed a positive association with incident lung cancer (OR 1.27, 95% CI 1.09‐1.44); however, this result was not consistently supported by the larger dataset of retrospective studies (OR 1.37, 95% CI 0.90‐1.83). Overall, studies in the lung displayed significant heterogeneity ( I 2 98%, P  < .0001), but no significant effect modification on the association between asthma and lung cancer was identified for the variables of sex, smoking or study design. Meta‐analysis could not be applied to the four papers reviewed in the skin, but three suggested an association between eczema and non‐melanoma skin cancer, while the remaining study failed to identify an association between melanoma and eczema. A single study meeting inclusion criteria showed no association between EoE and oesophageal malignancy. Conclusions: The current data cannot exclude the possibility of an association between atopy and malignancy the lung, skin and oesophagus. The relationship between allergy and cancer should be explored further in prospective studies that any association identified between these conditions has the potential for significant public health implications.